Evaluation of primary production in the northeastern Japan Sea on the base of shipboard and satellite data - V. I. Zvalinsky; P. V. Lobanova; P. Ya. Tishchenko; V. B. Lobanov (Известия ТИНРО, 2018)
Satellite data on chlorophyll concentration from ESA (CCI-OC) and Goddard Space Flight Center, NASA and shipboard observations of CTD, P, N, Si, inorganic carbon, DCI, and Chl a at 38 stations in the northeastern Japan Sea (46th cruise of RV Academik M.A. Lavrentyev on July 9–19, 2009) are analyzed. The highest chlorophyll concentrations were found in the subsurface layer (depth 20–40 m) or even deeper in the Polar Front zone, so they were not reﬂected in the satellite data. The minimal depths of the subsurface maximum were observed northward from the Polar Front where the estimations of chlorophyll concentration in the upper optical layer (Zd = 1/kd) were similar for the shipboard and satellite measurements (on average 0.384 ± 0.160 mg/m3 and 0.406 ± 0.120 mg/m3, respectively). Primary production was calculated using the assimilation number 4.46 mgC/mgChl per hour. Depth of euphotic layer was estimated using the vertical profles of nutrients and Chl a. Within this layer, the primary production in the northeastern Japan Sea was evaluated for the shipboard stations as 895–2275 mgС.m–2.day–1, on average 1450 ± 430 mgС.m–2.day–1, and for the satellite data on average 770 ± 190 mgС.m–2.day–1. The estimations based on the shipboard and satellite data were weakly correlated. The shipboard estimations exceed considerably the results obtained by Koblents-Mishke et al. (1956, 1970) and Yamada et al. (2005). Poor accuracy of satellite estimations of primary production is concluded because the deeper part of the euphotic layer with the maximum concentration of chlorophyll is in shadow for satellite sensors.